2015
DOI: 10.5493/wjem.v5.i2.77
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome and cardiovascular disease: The influence of C-reactive protein

Abstract: Obstructive sleep apnea syndrome (OSAS) is a common medical condition, associated with atherosclerosis and cardiovascular disease (CVD). The underlying pathophysiologic mechanisms of this association have not been completely understood and may be multifactorial in origin. A number of studies suggest that inflammatory processes have emerged critical in the pathogenesis of CVD in OSAS. A range of circulating inflammatory molecules has been identified and measured, with a view to assess inflammation and predict v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 81 publications
0
18
0
2
Order By: Relevance
“…Kritikou et al [48] reported some difference between apneic males and females: male OSAS subjects showed increased levels of CRP, IL-6 and TNF-receptor 1, and female OSAS subjects also showed higher CRP levels than controls. The short-term cPAP treatment did not improve the markers of inflammation [48]; at least 3 months of treatment were needed to reduce CRP levels [42].…”
Section: Systemic Inflammationmentioning
confidence: 96%
See 2 more Smart Citations
“…Kritikou et al [48] reported some difference between apneic males and females: male OSAS subjects showed increased levels of CRP, IL-6 and TNF-receptor 1, and female OSAS subjects also showed higher CRP levels than controls. The short-term cPAP treatment did not improve the markers of inflammation [48]; at least 3 months of treatment were needed to reduce CRP levels [42].…”
Section: Systemic Inflammationmentioning
confidence: 96%
“…C-reactive protein (CRP) is an acute-phase protein produced by the liver and is one of the most studied biomarkers of lowgrade inflammation in cardiovascular diseases, as it is a risk factor for atherosclerosis and cardiovascular morbidity and mortality [42]. Several researchers have evaluated the role of CRP in OSAS with conflicting results, probably due to the presence of obesity or pre-existing CAD [42].…”
Section: Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos estudios han asociado una proporcionalidad directa entre los niveles de PCR y el grado de adiposidad visceral, por lo que en la Figura 2 se observaría un incremento significativo en los niveles de PCR, lo cual representaría que la hipoxia produciría cambios en la expresión génica mediados por factores de transcripción como el receptor antagonista de la interleucina 1 (IL-1ra), factor de necrosis tumoral (FNT) y el factor nuclear de interleucina 6 (IL-6) (9)(10)(11)(12)(13) .…”
Section: Discussionunclassified
“…Por otro lado, los niveles en suero de la proteína C-reactiva (PCR), marcador universal de inflamación, se ven aumentados en el SAHS y se correlaciona con el IAH 183,232 . Sin embargo, con el tratamiento de la AOS con CPAP se observan niveles diferentes de la proteína y, por tanto, no aclara su participación en la patogénesis del SAHS [233][234][235] .…”
Section: Inflamación En El Endotelio Por Hciunclassified